Assessing stability motor skills of five-to-six-year old and six-to-seven-year old obese children - Eka Oktavianingsih; Asih Nur Ismiatun (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2020)
This study aims to determine the differences in the stability of motor skills between five-to-six-year old and six-to-seven-year old obese children. A total of 30 obese children were involved as the participants including 15 children aged 5-6 years old and 15 children aged 6-7 years old. Paediatric Balance Scale (PBS) was used to measure the stability motor performance of all participants. The method of data analysis was by means of independent sample T-test with a P-value of 0.05 as the criterion for all statistical significance. The findings of this study revealed that there is a significant difference in stability motor skills in the parameter walking in a bearn, standing with one foot, and axial movement between five-to-six-year old and six-to-seven-year old obese children. Obese children aged 6-7 years old performed better stability motor skills compared to those aged 5-6 years old.